Assessment of Subsidies for Construction Businesses in Nigeria: Evolution from an Oil-Based Economy to an Infrastructural-Based Economy - Edoka Augustine Ijigah; Idris Omeiza David (Journal of Techno-Social, 2024)
Subsidies are financial or non-financial aids or support given to an economic sector, individual or organization by their government to promote the economy and achieve specific policy objectives. This study assessed the use of subsidies for construction businesses in Nigeria with a view to revolutionize the country from oil-based economy to infrastructural-based economy. A structured questionnaire was self- administered to 404 construction business stakeholders with 304 (75%) retrieved from the respondents. Findings revealed that buying and selling of construction materials with Mean Score (MS) of 3.97 is the most successful construction businesses in Nigeria. The major factors considered in rating construction business performance are profitability to the investor (MS=3.70), resource management and control (MS=3.68), and cost performance (MS=3.63). The study concluded that the establishment of construction related institutions (MS=3.97), enforcement of health, safety, and hazards prevention policies (MS=3.91), exchange rate moderation for construction business (MS=3.86), and implementation of the National Building Code (NBC) (MS=3.85) will grow the infrastructural economy. The study recommended that construction business subsidies will only be effective, if resources are adequately managed, fraudulent practices are curbed, high cost of construction materials reduced and corruption are decimated. In addition, currency should be stabilised to reduce inflation of the prices of construction materials.